2003
DOI: 10.1007/s11920-003-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Complex partial seizures and depression

Abstract: A long-recognized association exists between epilepsy and affective disturbance, especially depression. People with complex partial seizures that result from temporal lobe seizure foci are highly vulnerable to psychiatric disorders. Accurate diagnosis of such disorders is an important key to treatment. Interictal depression or dysphoria is the most clinically significant problem of this type. Pharmacotherapeutic treatments that have positive effects in other types of depressive illness are also effective for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 54 publications
1
0
1
2
Order By: Relevance
“…Frequent hospitalizations due to epilepsy also contribute significantly to depression [33]. This finding is potentially associated with observations that a more severe course of epilepsy contributes to emergence of depressive symptoms [51]. Our study demonstrated quantitatively with different hazard ratios that epileptic patients who visited outpatient clinics, used emergency services and were hospitalized more frequently had higher risks of developing psychiatric disorders.…”
Section: Discussionsupporting
confidence: 63%
“…Frequent hospitalizations due to epilepsy also contribute significantly to depression [33]. This finding is potentially associated with observations that a more severe course of epilepsy contributes to emergence of depressive symptoms [51]. Our study demonstrated quantitatively with different hazard ratios that epileptic patients who visited outpatient clinics, used emergency services and were hospitalized more frequently had higher risks of developing psychiatric disorders.…”
Section: Discussionsupporting
confidence: 63%
“…In the current sample, the presence of generalized seizure significantly predicted severity of depression. This result did not appear to corroborate previous evidence demonstrating that, in comparison to generalized seizures, focal seizures were associated with a higher risk of depressive symptoms [ 58 ]. On the other hand, this evidence substantiates previous findings in the literature indicating that patients diagnosed with generalized seizure are the most vulnerable to severe depression [ 59 , 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…У односу на тип епилепсије, психопатологија се посебно често јавља код болесника са комплексним фокусним нападима, односно са епилепсијом темпо-ралног режња (149,150). Према узроку епилепсије, психичке промене су далеко че-шће код симптоматске него идиопатске епилепсије.…”
Section: узроци психичких поремећаја код болесника са епилепсијомunclassified